(untitled) (Revista Española de Fisiología, 1969)
Unespecific Antibacterial Resistance Levels in Sera from Aliergic Patients Variations in the unespecific antibacte rial levels of sera from aliergic patients are evaluated by the study of the action of these sera (previously inactivated) on the respiration of Escherichia coli strains. Data from hypersensitive patiens sera of type dermic and respiratory are compared with normal sera. From these results it appears that the unespecific natural antibodies are most active in patients with dermatitis aliergic while their titer decrease in cases of pollinosis.